La motivación y su relación con la productividad en los trabajadores de la empresa pollería y restaurant Sabor Oriental, distrito de Iquitos, año 2022 - Saldaña Panduro, Sonia Guiliana (2022)
The objective of this research was to determine how motivation is related to productivity in the Pollería and Restaurant Sabor Oriental company, district of Iquitos, year 2022, the type of quantitative, non-experimental, descriptive and correlational research was used, the population is made up of 15 administrative workers of the Pollería and Restaurant Sabor Oriental, the survey was carried out on the entire study population, it was obtained as a result that there is a significantly positive relationship between the motivation and productivity of the workers of the company Pollería and Restaurant Sabor Oriental, district of Iquitos, year 2022 according to the Pearson correlation value, which is equal to 0.756**; furthermore, the sigma value (bilateral) is 0.001. When analyzing the dimensions of variable 1: Motivation, 14 people, almost 100% of the total number of people surveyed, place the motivation variable in the "medium" category, and only 6.7%, which corresponds to 1 person, place it in the "average" category. the “high” category; On the other hand, for variable 2: Productivity 8 people, just over 50% of the total number of people surveyed place the productivity variable in the “medium” category, and almost 50%, which corresponds to 7 people, places it in the category “ high"; it was concluded that for both variables they do not have an optimal category and need to be strengthened.